AN EFFICIENT COMPUTATIONAL TECHNIQUE FOR MULTI-DIMENSIONAL DIFFUSION MODELS INVOLVING ATANGANA-BALEANU FRACTIONAL OPERATORS - VIKASH KUMAR MEENA, MURLI MANOHAR GOUR; MANJEET KUMARI (Journal of Computational Analysis and Applications (JoCAAA), 2024)
In this paper, we propose a precise and analytical approach known as, the Shehu Transform Decomposition Method (STDM) to solve multi-dimensional fractional diffusion equations that model density dynamics in diffusive materials.These equations incorporate time-fractional derivatives, formulated using the Atangana-Balenu (AB) derivative. Our method integrates the Shehu Transform (ST) with the Adomian Decomposition Method (ADM) and utilizes Adomian polynomials to effectively handle nonlinear terms.